Monoglyceride synthesis by glycerolysis of methyl oleate on solid acid-base catalysts - Ferretti, Cristián Alejandro (2010)
The synthesis of monoglycerides by glycerolysis of methyl oleate, an unsaturated fatty acid methyl ester, was studied on acid-base solid catalysts as an alternative to the current commercial technology that uses liquid base catalysts. Initially, the reaction conditions such as catalyst particle size and stirring rate required for operating the four-phase semi-continuous reactor under a kinetically controlled-regime were determined. Then the optimization of the reaction parameters for achieving high monoglyceride yields was performed using MgO. MgO compared favorably with the corresponding homogeneously catalyzed process. In fact, when using high reaction temperatures (493-523 K), glycerol/methyl oleate molar ratios between 2 and 6, and catalyst/reactant ratios of about 30 g/mol, glycerolysis of methyl oleate yields up to 77% monoglycerides in 2 h, a much higher value than those usually obtained via the liquid base-catalyzed homogeneous process (40-60%). The acid-base site requirements for the glycerolysis reaction were investigated using single oxides with different electronegativities. A good correlation was found between the catalytic activity and the base site density. In addition, results show that glycerolysis of methyl oleate requires strong base sites such as those of MgO. © 2009 Elsevier B.V. All rights reserved.